Multidisciplinary Approach in Treating Undiagnosed Severe Temporo Mandibular Joint Ankylosis : A Case Report - Sandhi, Afriyanti; Pakpahan, Evie Lamtiur; Handayani, Siti; Bangun, Kristaninta (Lingkar Studi Bedah Plastik Foundation, 2012)
Background: Temporo Mandibular Joint (TMJ) ankylosis refers to bone or fibrous adhesion of the anatomic joint component and the ensuing loss of their function. The TMJ forms the very cornerstone of craniofacial integrity and hence its ankylosis in growing children adversely affects the growth and development of the jaws and occlusion. Difficulty in mouth opening and mastication, poor oral hygiene and rampant caries pose a severe physical and psychological burden in the tender minds of children. Patient and Method: Bony ankylosis on the right TMJ in a female patient was not diagnosed until the patient reached her early teens, at which the condition was treated by bony fusion release on the right condyle. We managed the patient for further orthognathic surgery (Le Fort I Ostoeotomy and Bilateral Sagittal Split Osteotomy) to correct the skeletal deformity. Result: In collaboration with the Orthodontist for pre-surgery and post-surgery orthodontic treatment, and Physiotherapist for mouth opening and masticatory muscles exercises, a good functional and aesthetic result was achieved. Summary: Multidisciplinary approach in treating severe TMJ ankylosis is mandatory to achieve the optimum results. Awareness among all plastic surgeon and dentist involved in the treatment of craniofacial pathologies in children must be build to allow early diagnosis and treatment.